Is College Students' Reading Habit Truly Related to Their Writing Ability? - Menik Winiharti; Djuria Suprato (Bina Nusantara University, 2020)
The research aimed to describe college students’ reading habits and find the relationship between their reading habits and their writing ability. The data were collected from 50 non-English Department students who took English subject whose content was English language skills, including reading and writing. A questionnaire about reading habits was created and distributed to these students. Then in the classroom, they were assigned to write an essay about a topic they like twice. The analysis was done by analyzing the questionnaire’s results on reading habits, then comparing these results with writing scores using a statistical program, SPSS. The findings show that generally, more than half of the respondents usually read, even though they do not read quite often. Most students think that reading contributes to writing, especially in vocabulary and gathering ideas. However, their reading habits do not have a correlation with their writing ability.